Automated measurement of unsaturated iron binding capacity is an effective screening strategy for C282Y homozygous haemochromatosis. Issue 3 (1st March 2000) - Hickman, P E; Hourigan, L F; Powell, L W; Cordingley, F; Dimeski, G; Ormiston, B; Shaw, J; Ferguson, W; Johnson, M; Ascough, J; McDonell, K; Pink, A; et al.
Abstract : BACKGROUND: C282Y hereditary haemochromatosis is an appropriate condition for population screening. Transferrin saturation, the best screening test to date, is relatively expensive, labour intensive, and cannot be automated. Unsaturated iron binding capacity is a surrogate marker of transferrin saturation and its measurement can be automated. AIMS: To evaluate a screening strategy for C282Y hereditary haemochromatosis in a tertiary hospital environment based on unsaturated iron binding capacity as the initial screening test. METHODS: Measurement of unsaturated iron binding capacity was adapted to the main laboratory analyser. An unsaturated iron binding capacity of less than 30 μmol/l was identified as an appropriate decision point and 5182 consecutive subjects were screened over 28 consecutive days. RESULTS: Of those screened, 697 had an unsaturated iron binding capacity less than 30 μmol/l. Of these, transferrin saturation was greater than 40% in 294. A total of 227 were able to be genotyped for the C282Y mutation. Nine subjects homozygous for C282Y were identified. Based on full cost recovery, affected persons were identified at a cost of Aus2268·77 per case (approximately US1496). CONCLUSION: Automated measurement of unsaturated iron binding capacity enables a cost effective, large scale population screening programme for C282Y hereditary haemochromatosis to be developed.